(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Relevance: Congenital cleft lip and palate (CCLP) is a severe malformation of the dental system, which is characterized by pronounced structural and functional disorders. Perhaps there is no other congenital deformity that significantly changes the shape of the face and leads to such significant anatomical and functional disorders ( Granchuk G.N., 1987; Mahkamov E.W. et al., 1987; Medvedev M.V., 2001; Amanullaev R.A. et al., 2013; FlinnW .,2006; Hugentobler .,2006; RecamanM ., 2006; SliferK . L. , 2006; BaskaranM . et al ., 2015 )